FACTORS INFLUENCING INTENTION TOWARDS ORGAN DONATION AMONG HEALTH PROFESSIONALS IN LADOKE AKINTOLA UNIVERSITY OF TECHNOLOGY TEACHING HOSPITAL, OSOGBO, NIGERIA (2014)
One of the greatest technological advancements in modern medical practice is the discovery that lives could be saved through Organ Donation (OD) and transplantation. However, there is an unmet demand for OD and transplantations because few people including Health Professionals (HPs) are willing to donate. Therefore, this study was conducted to identify the factors influencing intention to donate organs among HPs at Ladoke Akintola University of Technology Teaching Hospital, Osogbo. This descriptive cross-sectional study employed stratified random sampling technique using profession as the basis for stratification to proportionately select 410 HPs through balloting. A semi-structured interviewer-administered questionnaire was used to elicit information on socio-demographic characteristics, OD awareness, knowledge, attitude and intention to donate. Knowledge and attitude were measured on a 41-point and 15-point scales respectively. Knowledge score of ≤22 was rated as poor while attitudinal score of ≤9 was rated as negative. Intention to be Living Donors (LDs), Cadaveric Donors (CDs) or both were classified as willing and unwilling. Two In-Depth Interviews (IDIs) which was used to complement the quantitative data were conducted with two available doctors in organ transplantation-related fields and analysed using thematic approach. Quantitative data were analysed using descriptive statistics, Chi-square and logistic regression at p<0.05. Respondents’ mean age was 33.6±7.4 years and 57.9% were females. Majority (83.5%) were doctors (37.1%) and nurses (46.4%). Others (16.4%) were pharmacists, paramedics and Health Record Officers (HROs). Most (99.7%) respondents had heard about OD. Out of this, 70.8% were aware of OD requests in Nigeria. Majority had poor knowledge (80.2%) and negative attitude (72.3%) to OD. None had donated an organ before while 44.2% were willing to donate. Of those willing to donate, 29.3% preferred to be LDs alone while 49.4% preferred to be both LDs and CDs. The reasons adduced for willingness to donate were to save lives (19%) and if a loved one needed it (13.2%). Adverse health consequences (33.9%), fear of death (17.5%) and lack of conviction to donate (12.5%) were the reasons for unwillingness to become LDs. The reasons for unwillingness to be CDs included not having considered it (46.0%), its complicated process (23.4%) and religious implications (20.4%). Majority (73.6%) believed that education was imperative to promoting OD while 12.4% supported the use of incentives. Knowledge of OD was not significantly associated with OD intention. The proportion of doctors willing to donate (58.9%) was significantly higher than HROs (42.1%). Sex was a significant predictor of OD intention (OR: 2.2, 95% CI: 1.4-3.3) with males more willing to donate. Respondents with positive attitude to OD were more willing to donate (OR: 5.0, 95% CI: 3.1-8.1). The IDIs revealed that HPs were unwilling to donate due to fear and uncertainty of OD outcome. It was agreed that information about successful OD should be made available to the public. Intention to donate was influenced by sex and attitude. Health education strategies such as periodic workshops, handbills providing information to dispel existing fears and misconceptions about organ donations should be promoted especially among female health professionals.